Cosmogenic gamma-rays and neutrinos constrain UHECR source models - van Vliet, A; Alves Batista, R; Hörandel, JR (Sissa Medialab, 2017)
When ultra-high-energy cosmic rays (UHECRs) propagate through the universe they produce secondary neutrinos as well as photons, electrons and positrons (initiating electromagnetic cascades) in different kinds of interactions. These neutrinos and electromagnetic cascades are detected at Earth as isotropic extragalactic fluxes. The level of these fluxes can be predicted and used to constrain UHECR source models.